ECONOMIC SECURITY OF AN ENTERPRISE IN THE DIGITAL AGE: NEW DIMENSIONS, THREATS AND MANAGEMENT APPROACHES (Development Service Industry Management, 2024)
The article examines the evolution of approaches to understanding the essence of the economic security of an enterprise (in the context of transformational changes in the external and internal environment). It is shown that in the early stages of development (1990-2000) a protective approach focused on material resources and physical protection dominated. In 2000-2010, there was a transition to a resource-functional approach, which focused on the efficiency of using internal resources. The period 2010-2020 was marked by the establishment of a systemic risk-oriented approach, within which the economic security of an enterprise is considered as a comprehensive risk management in all areas of the enterprise's activity. Since 2020, the focus has shifted to an adaptive-innovative approach, which involves the integration of digital technologies, flexible management, forecasting and the use of artificial intelligence tools. The essence of the modern understanding of the concept of "economic security of an enterprise" as a comprehensive characteristic of the state of security, stability and ability to adaptation and development, which is ensured by the use of innovative management and technological solutions.The stages of the formation of the economic security system of the enterprise are determined and its gradual development is revealed - from a reactive model to an integrated strategic system. The interpretation of the economic security system of the enterprise in the time aspect is analyzed, its evolution is presented in tables, and the key characteristics of each stage are summarized. The feasibility of using an adaptive-innovative model in the conditions of digitalization and global challenges is substantiated. It is concluded that the modern economic security system of the enterprise should be based on the principles of anticipatory management, digital transformation and an integrated approach to risk management. The author proposes his own vision of an updated definition of economic security of the enterprise and the economic security system of the enterprise, taking into account new challenges and technological changes.
Keywords: economic security of the enterprise; economic security system; adaptability; strategic stability; innovation